Last of the Tai-Pans: Improving the Sustainability of Long-Term Financial Flows by Improving Hong Kong's Corporate Governance - Bryane Michael; Say Goo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Hong Kong leads the rank tables as an international financial centre. However, the data indicate that some parts of her corporate governance arrangements probably detract from – rather than contribute to – that leading position. In this brief, we show how excessive shareholding concentration, probably self-dealing, insufficient minority shareholder recourse to mechanisms aimed at protecting their investments, and Hong Kong's close links with several “tax havens” probably weaken Hong Kong's role as an international financial centre. We present 18 recommendations aimed at increasing the volume of international financial capital coming to the city by improving Hong Kong's corporate governance.
Keywords: G34; K22; 330; corporate governance; hong kong; corporate governance; hong kong